2007
DOI: 10.1086/515392
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Binary Pulsar PSR J1744−3922: Radio Flux Variability, Near‐Infrared Observation, and Evolution

Abstract: PSR J1744À3922 is a binary pulsar exhibiting highly variable pulsed radio emission. We report on a statistical multifrequency study of the pulsed radio flux variability which suggests that this phenomenon is extrinsic to the pulsar and possibly tied to the companion, although not strongly correlated with orbital phase. The pulsar has an unusual combination of characteristics compared to typical recycled pulsars: a long spin period (172 ms); a relatively high magnetic field strength (1:7 ; 10 10 G); a very circ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Like our discovery, PSR J1744−3922 also exhibits nulling and is visible for approximately 25 % of the time at 1.4 GHz. PSR J1744−3922, and thus PSR J1726−31, might be the members of a new class of binary pulsars as proposed by Breton et al (2007): these binary pulsars have long spin periods, large magnetic fields (∼ 10 10−11 G), low-mass companions, and low orbital eccentricities. Their evolutionary history is not well understood and known formation channels fail to explain all of their properties.…”
Section: Psr J1726−31mentioning
confidence: 89%
“…Like our discovery, PSR J1744−3922 also exhibits nulling and is visible for approximately 25 % of the time at 1.4 GHz. PSR J1744−3922, and thus PSR J1726−31, might be the members of a new class of binary pulsars as proposed by Breton et al (2007): these binary pulsars have long spin periods, large magnetic fields (∼ 10 10−11 G), low-mass companions, and low orbital eccentricities. Their evolutionary history is not well understood and known formation channels fail to explain all of their properties.…”
Section: Psr J1726−31mentioning
confidence: 89%
“…AIC is anticipated to be responsible for the population of slow isolated pulsars with high magnetic fields in GCs (e.g. Lyne et al 1996;Breton et al 2007) and to be the origin of some slow accreting X-ray pulsars in the field such as 4U 1626−67 (e.g. Yungelson et al 2002), though it has never been observed directly.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this, it has been suggested that the NS in 4U 1626−67 was recently formed via AIC (Yungelson, Nelemans & van den Heuvel 2002). Several radio pulsars in the Galaxy possess relatively high B fields and long periods, with low‐mass companions in low‐eccentricity orbits (Breton et al 2007). They argue that these systems can be well‐explained through AIC.…”
Section: Radio Pulsar Modellingmentioning
confidence: 99%